177. Lentiviral Vector Mediated ADA Gene Transfer in ADA-Deficient SCID Mice - Carbonaro, Denise A; Jin, Xiangyang; Senadherra, Dinithi; Pepper, Karen; Petersen, Denise; Yu, Xiao-jin; Skelton, Dianne; Kohn, Donald B (Molecular therapy, 2004)
Genetic deficiency of adenosine deaminase (ADA) is responsible for ∼20% of human severe combined immune deficiency (SCID). While promising results have been obtained by Aiuti and co-workers using oncoretroviral vectors to transduce CD34+ cells from the bone marrow of ADA-deficient SCID patients, lentiviral vectors may lead to higher levels of ADA gene transfer that could extend benefits to older subjects with less transducible bone marrow or allow lower dosages of cytoreductive therapy to be used. We have constructed a SIN HIV-1-based lentiviral vector, SMPU-R-MND-ADA, which was produced at high titer (1 × 10e10 i.u./ml after 100-fold concentration) using VSV-G pseudotype and have shown it to express high levels of ADA enzyme activity in human and murine cell lines in vitro. A model of ADA-deficient SCID was produced by Rodney Kellems and co-workers (U.Texas, Houston) by ADA gene knock-out and rescue of neonatal lethality with an ADA mini-gene expressed in the placenta during gestation. These mice die from a non-infectious pulmonary disease within the first month of life, unless maintained on enzyme replacement therapy (ERT) with PEG-ADA. We have determined that transplantation of newborn ADA -/- mice with normal congenic bone marrow allows long-term survival without PEG-ADA and facilitates breeding.We have transduced whole ADA deficient marrow ex vivo which was then re-infused via the tail vein of 12 week old ADA -/- mice previously maintained on a low dose PEG-ADA ERT. After re-infusion of these transduced cells, the mipce were either maintained on a low dose PEG-ADA ERT which is analogous to no ERT dosage in a human patient or on a high dose PEG-ADA ERT which is analogous to the ERT regimen used in human ADA-deficient patients. The effects of high-dose PEG-ADA ERT on gene marking and the selective advantage of ADA-transduced T lymphoid progenitors is being analyzed.The mice continue to thrive and receive ERT, however, at one month no proviral marking was observed in PBL DNA samples.To produce ADA enzyme systemically, we are using in vivo transduction of neonatal ADA-deficient SCID mice. We have injected neonates with SMPU-R-MND-ADA viral supernatant using 1.6 × 10e8 I.U./kg via the facial vein on d2. These mice were initially maintained on low dose ERT with PEG-ADA but were then weaned off after day 45. They have remained well and have received no further treatment for over a subsequent 60 days. Proviral marking leukocytes as determined by qPCR, reveals low, but consistent marking (several cells per 10,000 cells analyzed) in the ADA deficient (-/-) animals. We will continue to track marking and survival and will examine bio-distribution of the vector.These studies demonstrate the potential for lentiviral-mediated ADA gene transfer to ameliorate immune deficiency in this novel model by ex vivo and in vivo approaches.